DRIVING ETHICAL EXCELLENCE: THE ROLE OF AUTHENTIC LEADERSHIP IN VALUE CONGRUENCE, CREATIVITY, AND PERFORMANCE IN INDONESIAN ISLAMIC BANKING - Anita Kartika Sari; Nanik Kustiningsih; Tri Wahjoedi; Thinzar Win (Jurnal Manajemen dan Kewirausahaan, 2026)
This study bridges the gaps identified in the literature on authentic leadership, value congruence, and personal creativity in influencing employee performance in Islamic banking institutions in Indonesia. The research limits its scope to the instance of PT Bank Syariah Indonesia (BSI) by involving a number of branch offices in the Surabaya area. While previous studies have confirmed the leadership-performance relationship, few have investigated the moderating role of authentic leadership on an Islamic banking context based on ethics and values rooted in Sharia principles. Using a quantitative approach with 98 participants from several BSI branches, data were examined using Structural Equation Modeling (SEM). The results show that authentic leadership highly magnifies the role of value congruence and personal creativity towards Islamic banking performance. The novelty of this study relies on integrating Social Exchange Theory with Islamic values by focusing on achieving a balance between innovation and ethical compliance. In practice, the findings suggest that authentic leadership development programs in Islamic banking institutions need to be reinforced to produce innovation with ethics and to uphold organizational effectiveness.